Дерзкий рейд: [роман] / Георгий Свиридов - Свиридов Георгий Иванович (Военные приключения, 2019)
Экземпляры: аб. (2023) / Инвентарный номер: 59403 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 24 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6